Impact of PM2.5, relative humidity, and temperature on sleep quality: a cross-sectional study in Taipei - Nguyen Thanh Tung; Yueh-Lun Lee; Wen-Te Liu; Yuan-Chien Lin; Jer-Hwa Chang; Huynh Nguyen Xuan Thao; Hoang Ba Dung; Lam Viet Trung; Tran Phan Chung Thuy; Nguyen Thi Hien; Cheng-Yu Tsai; Chen-Chen Lo; et al. (Annals of Medicine)
Introduction TWe investigated impacts of particulate matter with an aerodynamic diameter of less than 2.5 μm (PM2.5), relative humidity (RH), and temperature on sleep stages and arousal.Materials and Methods A cross-sectional analysis involving 8,611 participants was conducted at a sleep center in Taipei. We estimated individual-level exposure to RH, temperature, and PM2.5 over 1-day, 7-day, and 30-day periods. Linear regression models assessed the relationship between these environmental factors and sleep parameters across different seasons. Mediation analysis was used to explore PM2.5, RH, and temperature roles in these relationships.Results A 1% increase in RH over 1 and 7 days was associated with changes in non-rapid eye movement (NREM) sleep stages and increases in the arousal index across all seasons. A 1°C increase in temperature over similar periods led to increases in rapid eye movement (REM) sleep. During cold season, changes in RH and temperature were linked to variations in arousal and NREM sleep stages. In hot season, RH and temperature increases were correlated with changes in NREM sleep stages and arousal. Across all groups, a 1-μg/m³ increase in PM2.5 levels was associated with alterations in NREM and REM sleep stages and increases in the arousal index. We found PM2.5 levels mediated relationships between RH, temperature, and various sleep stages, particularly in cold season.Conclusions Lower RH and temperature, contributing to deep sleep reduction and increased arousal, were influenced by elevated PM2.5 exposure, especially during colder months. Enhancing environmental quality and reducing PM2.5 levels may lead to improved sleep quality.